2014
DOI: 10.1590/s0103-90162014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Forage yield and nutritive value of Panicum maximum genotypes in the Brazilian savannah

Abstract: The narrow genetic variability of grasslands and the incidence of new biotic and abiotic stresses have motivated the selection of new Panicum maximum genotypes for use as forage for beef cattle in the Brazilian savannah. This study aimed to evaluate forage yield and nutritive value of P. maximum genotypes including 14 accessions (PM30 to PM43), four intraspecifi c hybrids (PM44 to PM47) and six cultivars (Aruana, Massai, Milênio, Mombaça, Tanzania and Vencedor), examining 24 genotypes over two years (2003 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 16 publications
(22 reference statements)
3
28
2
3
Order By: Relevance
“…These results suggest that the P. maximum cultivars available in the market are not the most suitable for use in animal production systems in the Agreste, supporting the desirability of studies aimed at identifying forages adapted to the region. The highest LDM yield for PM34 was also observed by Fernandes et al (2014) evaluating the same genotypes in the Brazilian savannah. According to these authors, P. maximum is well suited to the soil and climate conditions of savannahs.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…These results suggest that the P. maximum cultivars available in the market are not the most suitable for use in animal production systems in the Agreste, supporting the desirability of studies aimed at identifying forages adapted to the region. The highest LDM yield for PM34 was also observed by Fernandes et al (2014) evaluating the same genotypes in the Brazilian savannah. According to these authors, P. maximum is well suited to the soil and climate conditions of savannahs.…”
Section: Methodsmentioning
confidence: 71%
“…is the most productive seed-propagated forage species available, and is an excellent option for diversifying and intensifying the use of Brazilian pastures Valle, 2008). In view of its high productivity, studies investigating the adaptation of this crop species to the Agreste region could indicate accessions and/or cultivars for use in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Megathyrsus maximus cultivars are mainly used in intensive cattle systems in Brazil, and M. maximus is a high‐yielding species (Fernandes et al ., ). The herbage accumulation of M. maximus in the current study was similar to that reported by Fernandes et al .…”
Section: Discussionmentioning
confidence: 99%
“…The herbage accumulation of M. maximus in the current study was similar to that reported by Fernandes et al . (, ~12 t ha −1 ), who compared the herbage accumulation of 24 genotypes of M. maximus . These authors highlighted that the productivity of M. maximus cv.…”
Section: Discussionmentioning
confidence: 99%
“…Brachiaria) is the most dominant, representing 50% of pastures of the country because of its remarkable adaptability and productivity in tropical climate conditions (Cabral et al, 2014;Demarchi et al, 2016). However, despite being more challenging and demanding for soil fertility, the use of Megathyrsus maximus is increasing as an option to forage grass due to its high-leaf production and nutritional value, factors that may allow the achievement of a superior animal performance (Fernandes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%